Application of the diathesis–stress model in therapy of children who stutter - Jastrzębowska-Jasińska, Aleksandra (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The article presents a new approach in the interpretation of the diathesis–stress model in relation to stuttering in children. Describes a modified model comprising three elements: diathesis, in the form of factors predisposing to the onset and persistence of stuttering, stress understood as an emotional event or change in the child’s life that triggers susceptibility, and protective factors understood as factors supporting the child’s mental immunity that indirectly strengthen the child and allow it to maintain speech fluency. The Holistic Integrated Child Activity Program (CZAD) for stuttering children and their parents will also be described, whose theoretical basis is based on the diathesis–stress model.